Defending Vulnerable Security Protocols by Means of Attack Interference in Non-Collaborative Scenarios - Fiazza, Maria-Camilla; Peroli, Michele; Viganò, Luca (Frontiers in ICT, 2015)
In security protocol analysis, the traditional choice to consider a single Dolev-Yao attacker is supported by the fact that models with multiple collaborating Dolev-Yao attackers are reducible to models with one Dolev-Yao attacker. In this paper, we take a fundamentally different approach and investigate the case of multiple non-collaborating attackers. We formalize a framework for multi-attacker scenarios and show, through a case study, that concurrent competitive attacks can interfere with each other. It is then possible to exploit interference to provide a form of defense to vulnerable protocols.